A latitudinal gradient study of common anti-infectious agent antibody prevalence in Italy and Colombia (2008)
Background: Infectious agents are important in the pathogenesis of autoimmune disease since they are a major part of the environmental trigger of autoimmunity. A negative relationship between latitude and infectious disease species richness has been suggested. Objectives: To examine whether their prevalence differs in two latitudinally different populations. Methods: The prevalence of infections with Toxoplasma gondii, rubella virus, cytomegalovirus, Epstein-Barr virus and Treponema pallidum was compared between subjects from Italy and Colombia. Results: We found high titers of antibodies against four of five microorganisms tested, Toxoplasma gondii (50.8%), rubella virus (German measles) (75%), cytomegalovirus (86.3%), Epstein-Barr virus (83.3%) and Treponema pallidum (6.3%) in completely healthy individuals from a tropical country (Colombia) and a European country (Italy). Differences between two groups of volunteers were noted regarding two infectious agents. The prevalence of immunoglobulin G anti-rubella antibodies was significantly higher among Italian subjects (85% vs. 67.9%, P = 0.002), whereas antibodies against CMV were less prevalent among Italian as compared to Colombian subjects (77% vs. 92.9%, P less than 0.001). Conclusions: These differences might also result in a different tendency towards development of autoimmune diseases associated with these infectious agents in different populations.